Laser-driven ablation through fast electrons in PALS-experiment at the laser radiation intensity of 1–50 PW/cm2. (March 2014) - Gus'kov, S. Yu.; Demchenko, N.N.; Kasperczuk, A.; Pisarczyk, T.; Kalinowska, Z.; Chodukowski, T.; Renner, O.; Smid, M.; Krousky, E.; Pfeifer, M.; Skala, J.; Ullschmied, J.; et al.
Abstract: The paper is directed to the study of high-temperature plasma and ablation plasma formation as well as efficiency of the laser energy transfer to solid targets irradiated by laser pulses with intensities of 1–50 PW/cm 2 and duration of 200–300 ps, i.e., at conditions corresponding to the characteristics of the laser spike designed to generate the igniting shock wave in the shock ignition concept. The experiments have been performed at Prague Asterix Laser System. The iodine laser delivered 250 ps (full width at half maximum) pulses with the energy in the range of 100–600 J at the first (λ1  = 1.315 µm) and third (λ3  = 0.438 µm) harmonic frequencies. The focal spot radius of the laser beam on the surface of Al or Cu targets made was gradually decreased from 160 to 40 µm. The diagnostic data collected using three-frame interferometry, X-ray spectroscopy, and crater replica technique were interpreted by two-dimensional numerical and analytical modeling which included generation and transport of fast electrons. The coupling parameter I λ 2 was varied in the range of 1 × 10 14 −8 × 10 16  Wμm 2 /cm 2 covering the regimes of weak to intense fast electron generation. The dominant contribution of fast electron energy transfer into the ablation process and shock wave generation was found when using the first harmonic laser radiation, the focal spot radius of 40–100 µm, and the laser energy of 300–600 J.